Study on anti-collision behavior of new precast concrete curb components in a highway tunnel - Li, Changjun; Zou, Junpeng; He, Wenbin; Ding, Xianying; Zheng, Guoping; Zhuang, Yizhou; Wang, Man (Frontiers in Earth Science, 2022)
In order to improve the prefabrication level of highway mountain tunnels, improve the quality of the project, and shorten the construction period, a new type of prefabricated concrete curb member was developed based on an actual project. The production process, construction technical points, and on-site assembly technology are discussed. In addition, a method to calculate the anti-collision performance of the curb components is proposed, that is, the collision force of 850 kN was calculated by the pseudo-static method, and then finite element simulation analysis was used to obtain the stress of the concrete structure and reinforcement. The results show that the reinforcement will not fail, which will ensure the curb component will not undergo brittle fracture. This study provides a reference to improve the prefabrication level of highway tunnels.